Feminismo, postmodernidad e Historia Antigua. Entre la igualdad y la diferencia - Cascajero, Juan (Gerión. Revista de Historia Antigua, 2002)
Only the permanent conscience, in women and men, of the negative discrimination (past and present) it can justify and to impel, for the sake of the equalityautonomy, the woman’s absolutely indispensable positive discrimination in the daily life, in the politics... and in the historiography. The clarification of the equality- difference conflict facilitates the understanding of today’s feminism and, therefore, it also enables the acceptance and use by the antiquity scholars of its theoretical as well as practical contributions.